PEMETAAN TREN GLOBAL DALAM PENELITIAN PEMBELAJARAN BERBASIS PERMAINAN DIGITAL: TINJAUAN BIBLIOMETRIK (2001–2024) - Umi Rosyidah; Purwanto Purwanto; Putri Taqwa Prasetyaningrum (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The rapid advancement of digital technology has driven the rise of Digital Game-Based Learning (DGBL) as an innovative educational approach. Yet, the field’s research themes, key actors, and future directions remain insufficiently mapped. This study conducts a bibliometric analysis of international publications from 2001 to 2024, using Scopus and IEEE databases, with the number of data analyzed as many as 5,854 scientific articles, to identify leading keywords, authors, institutions, and countries, examine major issues and sources, and trace the evolution of themes and emerging topics. Results indicate that educational games and game-based learning remain central, while frontier technologies such as artificial intelligence and augmented reality have proliferated since 2018. Research trends cluster into emerging (AI, AR, cybersecurity, critical thinking), established (GBL, e-learning, curricula, cognitive training), and declining (CAI, aggression, action video games) topics. Network analysis shows that the United States dominates at around 30%, Spain at 17%, and the United Kingdom at 14%. In practice, they offer opportunities for innovative instructional design that leverage AI for adaptive systems and AR for immersive educational experiences. In addition, the opportunity to develop new conceptual models that explain how games can function as adaptive learning ecosystems, combining pedagogical theory, cognitive psychology, and digital technology, is very open.